AlTaftazani,s comments on AlZamakshari,sAlKashaf (Journal of Hama University, 2019)
This research shows the amendments of Massoud Bin Omar Bin AbdulahSaadAldeenAlTaftazani (792h) in his explanation of the file Alkashaf(AlZamakshari).His annotation has high scientific value, and it had the admiration of the later authors. It contained at its pages grammatical, morphological, linguistic, rhetorical and philological…..matters, in spit, the explainer did not complete it because he died.I started the research with an introduction in which I presented the author,AlTaftazaniandhis annotation and stopped at the presentation of author andhisAlkashaf for his fame and needless for  presentation. I stopped at the annotation taking from it what AlTaftazani.Had taken on AlZamakshari, sAlKashaf,so Imentionedthe author's speech, which was the topic of the expliner'smendment. Then I mentioned the text of the explineron, which was commented, summarizing tha comment, mentioning other opinions to discuss the matter, and consider the wright opinion. It is important to mention that, Itoke some models of the comments, which suit the written essay.